SYNTHESIS AND CHARACTERIZATION OF GUAR GUM DERIVATIVES WITH ANTIOXIDANT MOIETIES - DURE NAJAF IQBA,; ERUM AKBAR HUSSAIN,; NARJIS NAZ, (International Journal of Pharma and Bio Sciences, 2013)
The purpose of this research is to introduce new green, nontoxic, cost effective derivatives of guar gum with antioxidant moieties covalently bounded to guar backbone. Guar gum is one of the significant naturally occurring non-ionic polysaccharide which has wide applications due to its rheological modifying properties in medicinal industrial and other commercial sectors. The amendment of rheological properties of guar gum can improve and diversify its commercial applications. A novel and efficient synthesis of five different new derivatives of guar gum (3a-3e) were prepared by insitu activation of caffeic, cinnamic, coumaric ferulic, and hydrocinnamic acid with dicyclohexylcarbodiimide (DCC) and N,N-dimethylaminopyridine (DMAP). Temperature Effect, reactants concentration and time interval played imperative role for determining the degree of substitution (DS) in all synthetic guar esters. The DS value was estimated quantitatively by titration method. Guar derivatives with variable DS were prepared and confirmed by FT-IR and 1H-NMR spectroscopy. Surface morphological study of new eco-friendly guar esters were achieved by scanning electron microscopy (SEM).